Association between the dietary index for gut microbiota and cardiometabolic multimorbidity: systemic immune-inflammation index and systemic inflammatory response index - Hu, Sihan; Song, Jiayuan; Jiang, Hui; Wei, Baojian; Wang, Hui (Frontiers in Nutrition, 2025)
ObjectiveThis study targets to investigate the connection between the possibility of Cardiometabolic Multimorbidity (CMM) and the Dietary Index for Gut Microbiota (DI-GM), paying special attention to the mediating roles of systemic inflammatory markers, specifically the Systemic Immune-Inflammation Index (SII) and the Systemic Inflammatory Response Index (SIRI).MethodsA cross-sectional study was conducted involving 17,388 eligible participants from the National Health and Nutrition Examination Survey (NHANES) spanning from 2007 to 2020. Weighted logistic regression model was employed to assess the correlation between DI-GM, SII, SIRI, and CMM. Additionally, restricted cubic spline (RCS) regression model was utilized to investigate any potential nonlinear relationships between these variables and the risk of CMM. The degree to which SII and SIRI mediated the link between CMM and DI-GM was assessed using mediation analysis. Additionally, sensitivity and subgroup analyses were conducted to confirm the results.ResultsA lower risk of CMM was markedly correlated with higher DI-GM scores (OR = 0.94, 95% CI: 0.91–0.98, p = 0.001). An elevated risk of CMM was markedly linked to higher levels of Ln-SII and Ln-SIRI (OR = 1.45, 95% CI: 1.28–1.65, p < 0.001; OR = 1.87, 95% CI: 1.69–2.07, p < 0.001). Higher education levels were associated with a stronger protective effect of DI-GM on CMM, according to subgroup analysis (P for interaction < 0.05). SII and SIRI, which accounted for 8.3 and 18.1% of the total effect, respectively, partially mediated the link between DI-GM and CMM (p < 0.001). Sensitivity analysis proved the stability of the findings.ConclusionAccording to the study’s findings, DI-GM could mitigate the danger of CMM. Reduced systemic inflammation acted as a partial mediating factor in this connection. These findings highlight the mechanisms of gut microbiota to mitigate the danger of CMM from a nutritional perspective. This offers insightful information for clinical CMM therapy and prevention.